AB0015 IDENTIFICATION OF KEY GENES TO SUPPORT SYSTEMIC LUPUS ERYTHEMATOSUS, RHEUMATOID ARTHRITIS AND ANKYLOSING SPONDYLITIS DIAGNOSIS BY TRANSCRIPTOMIC APPROACH. (2nd June 2020) - Mashayekhi Sardoo, A.; Leo, P.; Santos, M.; Costa, T.; Almeida, S. F.; Maia, S.; Benes, V.; Brown, M.; Branco, J.; Pimentel Dos Santos, F.
Abstract : Background: Early diagnosis of inflammatory rheumatic diseases (IRD), as Systemic Lupus Erythematosus (SLE), Rheumatoid Arthritis (RA) and axial Spondyloarthritis (axSpA) represents in our days a major clinical challenge. Increasing evidence has determined that early diagnosis, prompt treatment initiation and early achievement of remission are the best predictors of long-term clinical, functional and radiographic outcomes. Therefore, identification of sensitive biomarkers to support an early diagnosis to enable early therapy is of utmost importance [1, 2]. Objectives: This study aims to identify novel genes that may improve the current clinical diagnosis approach for early SLE, RA and axSpA. Methods: A cross-sectional study was conducted on 44 participants, 12 with axSpA (according to ASAS criteria), 11 with RA (according to ACR/EULAR criteria for RA), 10 with SLE (according to ACR classification criteria for SLE) and 11 Healthy Controls (HC), gender and age matched. Patients with co-occurrence of other IRD or having received biological therapies were excluded. Peripheral blood samples were collected into PAXgene tubes and stored in -80°C. mRNA profiling by RNA-seq was performed. Unpaired t-tests with multivariate permutation correction were applied to identify differentially expressed genes (DEGs) between patients and HC for each disease and within diseases. Enrichment analysis, Gene ontology (GO) and Kyoto Enrichment of Genes and Genomes (KEGG) analysis were also performed. DEGs that allow to distinguish each disease from HC and between diseases. The top DEGs (axSpA n=2, RA n=2, SLE n=3) identified were confirmed by quantitative RT-PCR. Results: For axSpA, genes involved in negative regulation of cytokines by JAK/STAT pathway and in osteoblast differentiation through STAT3 pathway, were confirmed. In SLE, genes involved in trap for immune complexes in peripheral blood and involved in nucleosome regulation, were also confirmed. Regarding RA, no genes were confirmed. Conclusion: Our work provides new insights into IRD pathogenesis, and discloses new biomarkers, which may be useful as either predictive biomarkers for diagnosis or therapeutic targets to improve IRD approach.Further validation are needed in different cohorts. References: [1]Monti, S. et al. (2015) 'Rheumatoid arthritis treatment: The earlier the better to prevent joint damage', RMD Open, 1(Suppl 1), pp. 1–5. doi: 10.1136/rmdopen-2015-000057. [2]Oglesby, A. et al. (2014) 'Impact of early versus late systemic lupus erythematosus diagnosis on clinical and economic outcomes.', Applied health economics and health policy, 12(2), pp. 179–90. doi: 10.1007/s40258-014-0085-x. Acknowledgments: To all patients and healthy controls who participated in the study Disclosure of Interests: Atlas Mashayekhi Sardoo: None declared, Paul Leo: None declared, Mariana Santos: None declared, Tiago Costa: None declared, Sergio Fernandes Almeida: None declared, Sara Maia: None declared, Vladimir Benes: None declared, Mattew Brown Speakers bureau: MSD, Pfizer, Novartis, Jaime Branco Speakers bureau: Vitoria, Fernando Pimentel dos Santos Speakers bureau: Novartis, Pfizer, Biogen, Vitoria,